GADAMER’S HERMENEUTICAL THOUGHT AND HABERMAS’S CRITIQUE - Yeremias Jena (Peminat Ilmu Ushuluddin, 2021)
As long as humans always try to understand the deepest meaning of a text, symbol, or event, hermeneutics is a common activity. However, the gap between the creation of texts, symbols or events has created its own problems that must be solved. The problem is, should an attempt at interpretation of a text, symbol or event achieve its objective status in the sense intended by the author or writer, or not? Hermeneutic thinkers differ in solving this problem. Unlike Friedrich Schleiermacher and Wilhelm Dilthey who emphasized the importance of revealing the author’s original intent, Hans-Georg Gadamer emphasized the importance of the subjective dimension of the interpreter. In Gadamer’s thought, prejudice and cultural influences in interpreting a text, symbol or phenomenon are also considered as one of the horizons. Dialectic and horizon fusion in itself will be an internal mechanism to reduce the dominance of prejudice or subjectivity that cannot be accounted for. By paying close attention to Jurgen Habermas’s note that hermeneutics overemphasize the aspects of prejudice and cultural influences will only provide opportunities for certain communication distortions and cultural hegemony, Gadamer’s contribution can still be maintained as a human hermeneutical activity.